The burden of consciousness : object animism in children's literature - Yam, Hui Qing (2009)
Animals, plants and objects are often anthropomorphized to delightful effect in children’s literature while adult depictions of the inanimate coming alive almost always occur in the genres of science fiction and horror and have had a much less positive spin. This essay argues that these negative evocations do indeed spill over into children’s texts, manifesting in the common motifs that appear in stories involving object animism, and that enlivened objects are furthermore, representations of Julia Kristeva’s concept of abjection.